Automated impact device based on phase synchronisation assessment for the enhancement of impact-synchronous modal analysis during operation / Lim Hong Cheet - Lim , Hong Cheet (2018)
Impact-synchronous Modal Analysis (ISMA) integrated with Impact-synchronous Time Averaging (ISTA) was introduced as a viable option for existing modal analysis techniques during operation. However, ISMA using manual impact hammer required a high number of impacts for better Frequency Response Functions (FRFs) estimation especially when the operating frequencies coincided with the natural modes. This finding has subsequently reduced the effectiveness and practicality of ISMA. Lack of control of impact timing using manual impact hammer has initiated phase synchronisation effect investigation and subsequent to the designs of auto impact device with different controlled impact events in order to fill the gaps from previous research. Firstly, phase synchronisation effect in ISMA during operation is investigated as in simulation studies and experimental testing. The assessment showed that a small amount of averaging, (i.e. up to 5 averages) is sufficient to eliminate the non-synchronous components by 98.48% on simulation and 95.22% on experimental modal testing under inconsistent phase condition. To enhance ISMA, it is known from the assessment that each impact applied must be non-synchronous with the periodic response of cyclic load. Thus, the auto impact device with non-synchronous impacts is designed where the impact frequency is a non-integer multiple of operating frequency. Implementation of this device in ISMA has reduced the dominant cyclic load component and second harmonic up to 45% and 17% respectively. Subsequently, all natural modes of interest are identified which is not achievable through manual impact hammer. Although the FRFs estimation is enhanced, a sharp peak originated from cyclic load is still observable. Hence, further reduction of cyclic load components is continued through a post-processing inconsistent phase selection assessment. When the selected impacts are non-synchronous with the cyclic load components, i.e., two pairs of data where the selected impacts in each pair is 180° difference, four averages or impacts are sufficient to reduce the first and second harmonics up to 82% and 52% respectively. Thus, the estimated FRF is strongly enhanced and good correlation is observed between modal extraction data and benchmark EMA. Utilising the outcomes from the assessment, a feedforward Automated Phase Controlled Impact Device (APCID) is designed in such a way that it is capable to adapt the updated phase difference information based on the electrical pulse signal of tachometer in each triggered time block of signal and uses this information to control the correct timing to impart an impact at the correct time/phase which is always non-synchronous with respect to the periodic response of cyclic load. Applying impact on the crest or trough or any phase position of the sinusoidal response due to cyclic load is then possible. Implementation of APCID in ISMA has reduced the first and second harmonics up to 92% and 55% respectively. In overall, a reduced number of averages thereby expedite the overall operational modal testing procedure, an improved of FRFs estimation and a good correlation of modal extraction data with benchmark data shown in this research has highlighted the advantages of ISMA using auto impact device based on phase synchronisation assessment.